Abundancia y biomasa de macroinvertebrados edáficos en la temporada lluviosa, en tres usos de la tierra, en los andes colombianos (2006)
COMPENDIO los usos evaluados fueron pastizal, cafetal y bosque secundario (Vereda Villa del Rosario, Aprox. 3º 33' 16â€? Latitud Norte y 76º 36' 01â€? Longitud Oeste, altitud 1.500 a 1.820m., precipitación 960 a 1.050 mm/año, 19.8 a 21.2º C) con la metodología TSBF. Se implementaron tres monolitos por uso y cada uno se subdividió en cuatro estratos (hojarasca, 0-10 cm, 10-20 cm, y 20-30 cm), las variables densidad y biomasa por parcela y estrato se examinaron a través de ANOVAS y Post-Anovas. En abundancia la supremacía fue de hormigas (25584 ejemplares), miriápodos (4808 ejemplares) y lombrices (1984 ejemplares), la diferencia significativa la marcaron los miriápodos (F=4.84, P=0.014) asociados con bosque y cafetal con sombrío. En biomasa los grupos más importantes fueron miriápodos (701.05 g m-2, 58.71%), lombrices (90.64 g m-2; 7.59%), chisas (27.07 g m-2; 2.26%) hormigas (20.90 g m-2; 1.75%) y arañas (15.71 g m-2 ; 1.31%), con diferencias significativas en hormigas (F=4.17, P=0.024) y arañas (F=3.43, P=0.4024); También hubo diferencias estadísticas significativas en la densidad y biomasa de macroinvertebrados y los estratos de los monolitos, los resultados indican que estos organismos expresan en su población y biomasa respuestas ambientales asociadas más con la estructura del agroecosistema que con la variación química, física o microbiológica del hábitat; se recomienda discriminar taxonómicamente los grupos funcionales y ampliar los muestreos a la temporada seca. Palabras clave: uso del suelo, macroinvertebrados edáficos, densidad, abundancia, agroecosistemas, Andes colombianos. ABSTRACT Abundance and biomass of soil macroinvertabrates during the rainy season in three land use systems in the Colombian Andes. Using the TSBF methodology, three land use systemsâ€”pastures, coffee plantation, and secondary forestâ€” were evaluated in the rural community of Villa del Rosario, located in the municipality of Cali, Valle del Cauca, Colombia . This community is located at approximately 3º 33' 16 N and 76º 36' 01 W, with an altitude of 1.500-1.820 m above sea level, an annual precipitation of 960-1.050 mm, and temperatures ranging from 19.8 to 21.2º C. Three monoliths were used per land use system, each one subdivided into four strata (fallen leaves and 0-10 cm, 10-20 cm, and 20-30 cm in depth). The variables for density and biomass per plot and stratum were submitted to ANOVA and post-ANOVA comparison. Among macroinvertebrates found, ants outnumbered the others by far with 25.584 individuals, followed by myriapods with 4808 individuals, and earthworms with 1984. A significant difference was found in the case of myriapods (F=4.84, P=0.014) in association with forest and coffee plantation under shade. In terms of biomass, the most important groups found were myriapods (701.05 g m-2, 58.71%), earthworms (90.64 g m-2, 7.59%), grubs (27.07 g m-2, 2.26%), ants (20.90 g m-2, 1.75%), and spiders (15.71 g m-2, 1.31%). Significant differences were found in the case of ants (F=4.17, P=0.024) and spiders (F=3.43, P=0.4024). Significant statistical differences were also found for density and biomass of macroinvertebrates and monolith strata. Results indicated that the environmental response of these organisms in terms of population and biomass is more associated to agroecosystem structure than to chemical, physical, or microbiological variation of the habitat. Functional groups should be taxonomically differentiated and samplings should be extended to the dry season. Key words: land use, soil macroinvertebrates, density, agroecosystems, Colombian Andes, biomass.